Current policies for promoting neglected and underutilized crop species in Burkina Faso and Niger - Rokka, Susanna; El Bilali, Hamid; Borelli, Teresa; Calabrese, Generosa J.; Lecci, Silvia; Otieno, Gloria; Tietiambou, Fanta Reine Sheirita; Bteich, Marie Reine; Grazioli, Francesca; Kabre, Blaise; Seindira, Magnini; Karambiri, Souleymane; et al. (Informa UK Limited, 2025)
Greater use of agrobiodiversity and especially neglected and underutilized species (NUS) like amaranth, Bambara groundnut, cassava, fabirama, okra, moringa, Guinea sorrel, or sweet potato can tackle climate change and food insecurity, and build food sovereignty. The role of NUS in policies and strategies in Burkina Faso and Niger has not been studied earlier. This study uses a mixed method where analysis of current policies, an online survey and workshops with stakeholders were combined. It gives an overview on policies on different sectors and helps to explore options for enhancing the efficiency of incentives aimed at promoting the use of NUS. The contribution of the policies and strategies (44 documents of the 96 identified) to the promotion of NUS and agrobiodiversity was analyzed. They generally recognize the importance of agroecological practices and biodiversity, and thus support the promotion of NUS. However, only 17 mention NUS specifically. Some texts refer to gender as a cross-cutting theme and recognize women’s primordial role in a better management of resources. Based on the findings, it is recommended to: (i) include NUS in sectoral policies; (ii) support the marketing and consumption; (iii) consider the best practices implemented in other countries to mainstream NUS in food systems.